2021
DOI: 10.1097/yco.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining treatment and prevention programs for opioid use disorders during the coronavirus disease 2019 pandemic

Abstract: Purpose of review The current article reviews the impact of the biggest health crisis for many decades, coronavirus disease 2019 (COVID-19), on opioid treatment programs and the strategies adopted for maintaining opioid treatment programs during the pandemic. Recent findings The difficulty of access to opioid treatment services and the mental health problems accompanying opioid use disorders are the two main challenges to maintaining accessible and effective opioid trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…While studies examining clinician attitudes have typically identified general barriers providing OAT (eg, concerns about “difficult” patients) rather than barriers associated with specific medications (eg, sublingual buprenorphine versus naltrexone), 96 methadone is subject to unique stigma 6 that may be compounded by its strict regulation. Retaining and expanding regulatory changes implemented during the COVID-19 pandemic to aid continuity of care 97 , 98 is increasingly been recognised an important step in developing innovative models of care to address the opioid crisis, 98 , 99 and may also reduce the stigma associated with methadone if treatment is made more accessible.…”
Section: Strategies To Reduce Stigmamentioning
confidence: 99%
“…While studies examining clinician attitudes have typically identified general barriers providing OAT (eg, concerns about “difficult” patients) rather than barriers associated with specific medications (eg, sublingual buprenorphine versus naltrexone), 96 methadone is subject to unique stigma 6 that may be compounded by its strict regulation. Retaining and expanding regulatory changes implemented during the COVID-19 pandemic to aid continuity of care 97 , 98 is increasingly been recognised an important step in developing innovative models of care to address the opioid crisis, 98 , 99 and may also reduce the stigma associated with methadone if treatment is made more accessible.…”
Section: Strategies To Reduce Stigmamentioning
confidence: 99%
“…These mental health issues lead to an enormous burden on the mental health system (MHS) in China. Min et al [7] review the impact of COVID-19 on opioid treatment programs in China. They find the biggest challenge is the difficulty of accessing opioid treatment services, including MMT, needle and syringe exchange programs.…”
Section: The Challenge and Response To The Drug Treatment In Chinamentioning
confidence: 99%
“…Several strategies were effective in maintaining opioid treatment programs during the COVID-19 pandemic. For example, we can allow patients with OUD take medication to home for a longer time, the mental health of people with OUD should not be neglected, and the psychological counseling for patients on MMT need to be strengthen during the COVID-19 epidemic to reduce the risk of substance abuse [7].…”
Section: The Challenge and Response To The Drug Treatment In Chinamentioning
confidence: 99%
See 2 more Smart Citations